Pengaruh Pemberian Informasi melalui Media Film Animasi terhadap Peningkatan Perilaku Kesehatan Gigi dan Mulut pada Siswa SDN Kedondong, Kecamatan Sokaraja, Kabupaten Banyumas - Haris Budi Widodo; Ryan Budi Purnama; Arcadia Sulistijo Junior; Dennia Dwi AFD (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2021)
Dental and oral health can directly affect the quality of life, and is a serious problem in Indonesia, especially in children. Based on the results of the Basic Health Research (Riskesdas) in 2018, 54% of children aged 5-9 years and 41.4% of children aged 10-14 years experienced dental caries. Dental and oral health is influenced by children's behavior which includes knowledge, attitudes, and actions. The objective of this study was to determine the effect of providing information through animated film media on improving dental and oral health behavior in students of SDN Kedondong, Sokaraja, Banyumas. Methods: This type of research is a pre-experimental design one group pretest- posttest by comparing behavioral values which include components of knowledge, attitudes and actions about dental and oral health before and after giving information through animated films, measuring the number of caries using the DMF-T/def-index. t, as well as the severity of dental caries that were not treated using the PUFA/PUFA index. The research population was students of SDN Kedondong while the number of samples was 60 people who were taken purposively by considering the inclusion-exclusion criteria. Data was collected using pre-test and post-test questionnaires and measurements of DMF-T, def-t, and PUFA/PUFA indexes. Data analysis used was non-parametric comparative Wilcoxon signed rank test because the data were not normally distributed. Results: This study showed that there was a significant difference (p<0.05). Dental and oral health behavior between before and after being given information through animated films to students at SDN Kedondong, Sokaraja, Banyumas effective in improving dental and oral health behavior in students of SDN Kedondong, Sokaraja District, Banyumas Regency.